2005
DOI: 10.1097/01.qai.0000160515.20581.ad
|View full text |Cite
|
Sign up to set email alerts
|

Absolute CD4 T-Cell Counting in Resource-Poor Settings

Abstract: Flow cytometry is an accurate but expensive method to determine absolute CD4 cell counts. We compared different methods to measure absolute CD4 counts in blood samples from HIV-infected and uninfected subjects using a research/clinical flow cytometer (FACScan); a dedicated clinical instrument (FACSCount); and a volumetric, mobile, open-system flow cytometer equipped with 3 fluorescence and 2 light scatter detectors (Cyflow SL blue). The FACScan and Cyflow were used as single-platform instruments, but they diff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2006
2006
2014
2014

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(10 citation statements)
references
References 13 publications
0
10
0
Order By: Relevance
“…Several North American studies have demonstrated consistent inter-laboratory variability in measurements despite shared protocols and participation in quality assurance programmes [23-25]. Due to the distance between laboratories we were unable to conduct comparability experiments on shared samples although comparison studies at one of the sites found no systematic variation in results between the two platforms even at low CD4 counts [26] as has been demonstrated in similar settings [27] and UK’s national external quality assurance programme shows no difference in mean CD4 count returns. It is possible that the recent exposure of the rural group to tuberculosis might have had an effect on CD4 count as it is known that active disease may depress the level [28].…”
Section: Discussionmentioning
confidence: 91%
“…Several North American studies have demonstrated consistent inter-laboratory variability in measurements despite shared protocols and participation in quality assurance programmes [23-25]. Due to the distance between laboratories we were unable to conduct comparability experiments on shared samples although comparison studies at one of the sites found no systematic variation in results between the two platforms even at low CD4 counts [26] as has been demonstrated in similar settings [27] and UK’s national external quality assurance programme shows no difference in mean CD4 count returns. It is possible that the recent exposure of the rural group to tuberculosis might have had an effect on CD4 count as it is known that active disease may depress the level [28].…”
Section: Discussionmentioning
confidence: 91%
“…The Auto40 analyzer uses a volumetric syringe moved by a stepper motor that draws and delivers a known sample volume. Therefore, its absolute volumetric counting allows the direct determination of the number of cells per unit of sample volume without the need for reference material such as micro beads [8,22]. Thus, direct volumetric CD4 T cell measurements were performed on the Auto40 using PE-conjugated anti-CD4 and PE-Dyomics649-conjugated anti-CD45 monoclonal antibodies (Apogee Flow Systems Ltd) for CD4 T cell count measurement.…”
Section: Methodsmentioning
confidence: 99%
“…Pressure is also used to deliver sample, but the volumetric delivery offered by precision syringe pumps enables the direct counting of cells or particles without the use of external microsphere counting standards that are used to precisely meter volumetric delivery rates. 59 Peristaltic pumps are also effectively used, but care must be taken to dampen fluidic pulses in such systems. 60 Overall, pressure driven flow with external pumps can generate a few μL/min up to several mL/min, as long as the microfluidic system can with stand the high pressure.…”
Section: B Microfluidics and Microfabrication In Flow Cytometrymentioning
confidence: 99%